Exploring Student Engagement in a Blended and Gamified Statistics and Probability: Designed with Learning Styles and Player Types - Gonowon, Reymund R. (Animo Repository, 2024)
Educators are called to contribute towards achieving SDG 4: Quality Education. A major determinant in achieving this goal is providing learners with essential skills such as analyzing and interpreting data, making inferences, and driving evidence-based decisions which are the expected competencies in Statistics and Probability (STATPRO), one of the core subjects of the senior high school curriculum in the Philippines. To progress towards SDG 4, achieving the learning competencies of STATPRO is vital, however engaging students in a blended learning environment may be challenging. This study aims to explore the behavioral engagement of students in a gamified STATPRO class through classroom action research. In this first iteration, activities were designed to cater to the student’s learning styles and player types, incorporating gamification elements such as choice, progress, experience points, badges, missions, and party and guilds. A descriptive analysis of the student logs and completion rates of tasks was implemented. Through a reflexive thematic analysis of reflection entries and a focus group discussion, the students’ experiences indicated a lack of motivation, difficulty understanding the gamification elements, and negative perceptions towards the subject. These results provide evidence that implementing a contemporary pedagogical approach in designing a course does not guarantee student engagement. After a prompt reflection, recommendations for the next iterations include rethinking the approach to the class, redesigning the activities, emphasizing choice, increasing the number of classes, integrating with other subjects, and gaining student and expert insights.